1995
DOI: 10.1192/bjp.167.3.390
|View full text |Cite
|
Sign up to set email alerts
|

Investigation by Linkage Analysis of the XY Pseudoautosomal Region in the Genetic Susceptibility to Schizophrenia

Abstract: We conclude that the present study provides no support for the involvement of either the pseudoautosomal region or the nearby region of the sex chromosomes in the aetiology of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A pseudoautosomal locus for a schizophrenia susceptibility gene that would account for these differences was suggested [Crow et al, 1989]. An early study using sib pair analysis reported evidence of excess sharing at DXYS14 [Collinge et al, 1991], that was supported in one nonparametric replication , but was not supported by a number of other studies using both parametric and nonparametric analyses Wang et al, 1993;Crow et al, 1994;Barr et al, 1994;Maier et al, 1995;Kalsi et al, 1995c]. A large collaborative study examining markers within band Xp11 near the MAO loci found a LOD of 1.97 under a dominant model for DXS7 in a set of 92 sib pairs selected for maternal inheritance.…”
Section: Chromosomementioning
confidence: 98%
“…A pseudoautosomal locus for a schizophrenia susceptibility gene that would account for these differences was suggested [Crow et al, 1989]. An early study using sib pair analysis reported evidence of excess sharing at DXYS14 [Collinge et al, 1991], that was supported in one nonparametric replication , but was not supported by a number of other studies using both parametric and nonparametric analyses Wang et al, 1993;Crow et al, 1994;Barr et al, 1994;Maier et al, 1995;Kalsi et al, 1995c]. A large collaborative study examining markers within band Xp11 near the MAO loci found a LOD of 1.97 under a dominant model for DXS7 in a set of 92 sib pairs selected for maternal inheritance.…”
Section: Chromosomementioning
confidence: 98%
“…Nevertheless, although initially promising [21][22][23], early molecular studies were never able to show a linkage or association with schizophrenia for any region of the sex chromosomes or variants in the genes located there, despite the existence of some good candidates [24][25][26][27][28][29][30][31]. Although there continued to be lack of data to support this hypothesis and interest waned among most investigators in pursuing it further, the sex chromosome hypothesis has never been clearly negated.…”
Section: Doi: 101159/000491489mentioning
confidence: 99%
“…However, the first smaller GWAS of schizophrenia performed demonstrated some evidence of SNPs associated with the X chromosome in their top results [13,30,31]. Wong et al [40] performed a GWAS of schizophrenia in the Han Chinese population and also examined a group of selected candidate genes from prior studies and plausible biological pathways.…”
Section: The Unbiased Screening Of the Genomementioning
confidence: 99%
See 1 more Smart Citation
“…The need for such methods is apparent from the numerous studies of schizophrenia that look at potential association with the XY region (Collinge et al 1991;Asherson et al 1992;Gorwood et al 1992;Wang et al 1993; Barr et al 1994;Crow et al 1994;d'Amato et al 1994;Maier et al 1994;Kalsi et al 1995); an excess of same-sex affected pairs has been observed in a few studies (Collinge et al 1991;Asherson et al 1992;Gotwood et al 1992), which has been interpreted as an…”
Section: Figurementioning
confidence: 99%